WEST, Paige. 2006. Conservation is our government now: the politics of ecology in Papua New Guinea. Durham and London: Duke University Press. - Radomsky, Guilherme F.W. (Campos - Revista de Antropologia, 2009)
Resenha do livro Conservation is our government now: the politics of ecology in Papua New Guinea, de Paige West, publicado em 2006.